MODERNITAS NAHDLATUL ULAMA: “BERMAIN-MAIN DIANTARA TRADISI(ONAL) DAN KE-MODERN-AN” - M U H A M M A D N U R K H O I R O N (Jurnal Dialog, 2017)
Nahdlatul Ulama’ (NU) might be deemed as traditional religious organization which rejected the modernity. Yet, it is rarely found the works tracing that NU was actually traditional religious organization. As time goes on, NU grows up and has been world-wide known either by academic scholars or common people. NU is no more labeled-traditional organization, because it has been capable to co-exist and could go hand in hand with modernity. The principal of Al-Muhafadhatu ‘Ala Qadim As-Shalih wa Akhdu bi Al-Jadid al-Ashlah (nurturing the existing culture as long as it is good or can be coloured by Islam, and adopting the new better one) and the involvement of some NU clerics to political practice and official government become the evidence that NU welcomes modernity. This article describes the role of NU to meet traditional and modern value. The success of NU to combine traditional and modern leads it to be as moderate organization. This article also scrutinizes historically and sociologically that NU is one of moderate Islamic movements in Indonesia.